2023
DOI: 10.23887/ijssb.v7i2.54939
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Support Mediates The Effect of Job Insecurity on Organizational Citizenship Behavior at Adiwana Unagi Suites

Ni Putu Vera Andriyanti,
IB Raka Suardana

Abstract: Facing the Covid-19 pandemic, the tourism sector, especially in the hospitality sector, must make several adjustments in order to survive, one of which is reducing the number of employees. This condition causes the remaining employees to do extra work so that the company can run. This study aims to determine the role of perceived organizational support in mediating the effect of job insecurity on organizational citizenship behavior. This research was conducted at Adiwana Unagi Suites. The population in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The organization can motivate employees to carry out their duties effectively and show appreciation for their contributions through incentives and bonuses.The study's findings align with Sadaf et al (2022) research, which demonstrated that an increase in perceived organizational support leads to a corresponding increase in job satisfaction. Similarly, Andriyanti & Supartha (2021) research also indicates a significant correlation between perceived organizational support and employee job satisfaction.…”
Section: Discussionmentioning
confidence: 83%
“…The organization can motivate employees to carry out their duties effectively and show appreciation for their contributions through incentives and bonuses.The study's findings align with Sadaf et al (2022) research, which demonstrated that an increase in perceived organizational support leads to a corresponding increase in job satisfaction. Similarly, Andriyanti & Supartha (2021) research also indicates a significant correlation between perceived organizational support and employee job satisfaction.…”
Section: Discussionmentioning
confidence: 83%
“…Findings in studies conducted by Mahmoud et al, (2021) concluded that job satisfaction predicts OCB positively. More studies by Aldrin & Yunanto (2019); Narzary & Palo (2020); Nurjanah et al, (2020); Andriyanti & Supartha (2021) found that job satisfaction has a significant and positive effect on organizational citizenship behavior.…”
Section: The Effect Of Job Satisfaction On Organizational Citizenship...mentioning
confidence: 99%
“…Kata kunci: kepuasan, kerja, leader, member, exchange, OCBBasirudin et al, 2016). Dalam beberapa perusahaan, terkadang terdapat OCB yang tidak maksimal sehingga perlu peran extra dari perusahaan untuk mengelola hal tersebut(Andriyanti & Supartha, 2021). OCB yang tidak maksimal yang terjadi pada PDAM Tirta Sembada, masih rendahnya partisipasi karyawan dalam membantu koleganya pada pekerjaan diluar tanggungjawab mereka.…”
unclassified